2021
DOI: 10.18332/ejm/143873
|View full text |Cite
|
Sign up to set email alerts
|

Iranian midwives’ awareness and performance of respectful maternity care during labor and childbirth

Abstract: INTRODUCTION Midwives' perceptions of Respectful Maternity Care (RMC) play an important role in promoting quality of care. This study aimed to explore the awareness and performance of Iranian midwives of RMC during childbirth. METHODS A cross-sectional study was carried out from November to December 2020 to evaluate 130 midwives' awareness and performance of RMC during childbirth at four public hospitals in Urmia province, Iran. Participants were midwives who were working in the labor unit and had at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…The results of a recent study by Haghdoost et al (2021) in Urmia showed that the midwives had a good knowledge and fair performance towards RMC [61], which is not consistent with our study. This inconsistency may be due to differences in the study population as well as data collection tools.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of a recent study by Haghdoost et al (2021) in Urmia showed that the midwives had a good knowledge and fair performance towards RMC [61], which is not consistent with our study. This inconsistency may be due to differences in the study population as well as data collection tools.…”
Section: Discussioncontrasting
confidence: 99%
“…Foreign studies confirmed the above thesis that the job satisfaction of midwives and the willingness to stay in a given job depend on what type of the leadership is being cultivated amongst the management [ 42 ]. In turn, Iranian research reports that a lack of job satisfaction has a significant negative impact on the quality of communication and patient care [ 43 ]. Swedish midwives, when assessing job satisfaction, emphasized the lack of professional recognition instead, drawing attention to the perceived conflict of roles and the feeling of burnout [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Every woman has the right to the best maternity care that is humanly possible, which includes the highest degree of health that is respectful (Belizan et al, 2020). Respectful maternity care (RMC) refers to seven domains that have been developed by White Ribbon Alliance and is a universal human right of childbearing women (RMC Charter) (WRA) (Haghdoost et al, 2021). Respectful maternity care may increase a woman's likelihood of giving birth vaginally, increase her satisfaction, and shorten her labor (Bohren et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This assistance comprises emotional support (constant presence, touching, empathy, reassurance, and praise) as well as knowledge about the status of the labor. Together with comfort measures, it might also offer guidance on coping mechanisms (Haghdoost et al, 2021). A number of variables contribute to disrespectful maternity care, among is the provider factors which include work overload/stress, training gaps, the desire for a positive obstetric outcome, under-remuneration and under-appreciation (Okedo-Alex et al, 2020).…”
Section: Introductionmentioning
confidence: 99%